Isolamento viral e diagnóstico molecular de herpevírus canino - Kurissio, Jacqueline Kazue [UNESP] (2013)
The canine herpesvirus (CHV-1) causes contagious disease affecting dogs worldwide. It is considered the responsible for cause reproductive problems, respiratory, eyes, neurologic changes may lead to death newborns and immunocompromised adults. Therefore, our study aimed to isolate CHV-1 from biological samples, standardize a diagnostic techniques for the detection of canine herpesvirus, verify the presence of infected dogs in São Paulo state and compare three modifications in the technique of limiting dilution in relation to molecular quantification to qPCR (by quantitative PCR to determine the viral titer). Thus, we collected 139 blood samples, organ´s fragments from 12 neonates death and 5 genital secretions samples with swabs of animals from kennels and households. After obtaining the DNA from samples were accomplished the qPCR (quantitative PCR) and snPCR (seminested PCR) assay for detection of CHV-1. It was found positivity in nine blood sample and organ´s fragments of an animal, the genital secretions samples were all negative. The viral isolation was performed from kidney. The infected cells showed cytopathic effects compatible with the CHV-1. Positive samples were sequenced showed 100% identity with the CHV-1 (Genbank™: X75765). The molecular techniques for detection agent were sensitive and specific, both the snPCR as the qPCR. In these techniques was enabled to detect DNA 15.35 copies/mL of blood samples and 1.15 copies/μg of tissue. The use of molecular techniques allowed the detection active infections of of HCV-1 with optimal detection limit. More studies are needed to understand the infection epidemiology of CHV-1 in the canine population in Brazil